(untitled) (Collection of scientific works «Scientific Problems of Architecture and Urban Planning» | ODABA, 2025)
The article «Innovative approaches to interior design» is devoted to identifying modern approaches to interior design, comparing these approaches with traditional ones, and establishing non-architectural factors that influence interior design. Interiors are shaped by architecture and design. The process of shaping is traditionally based on the experience and suggestions of fashion journals, but not all of these solutions are viable, not always elite – the advertising experiment correlates with the everyday life of users. The main innovation in the change of approaches is not the design that is accepted, but the rethinking of many life technologies. The transformation of constantly changing life technologies into material forms. Combinations of materialized life forms, their complexes and combinations become a factor of architectural and design creativity in the field of interior design. Interior design results in the design of environmental processes, situations, and is based on aesthetics of a different kind than the traditional one. The essence of interior design is not to make things beautiful, but to see beauty in everyday life and its processes. The task is to establish the methods and principles of design education of the environment, its implementation in professional design creativity. The article is aimed at finding the prospects of the profession, the potential of practice turns, which can be used as a basis for future creative searches. The sources of generating new ideas revealed. New approaches are illustrated by student works.